Diversity and Phylogenetic Analysis of Mosquito Species in Kole Wetlands of Thrissur, Kerala, and a Comparative Study on Susceptibility of Aedes albopictus (Skuse, 1895) and Culex quinquefasciatus Say, 1823, against Conventional Insecticides - Asha, A.V. (Christ College (Automomous), Irinjalakuda, 2023)
The Kole wetlands in Thrissur, Kerala, are a strip of shallow water that acts as an intermediate zone between terrestrial and marine ecosystems. They keep the water level between 0.5 to 1 meter below sea level and are situated in Kerala's central region, covering an area of 10187 hectares, spanning across the Mukundapuram, Chavakad, and Thrissur Taluks of the Thrissur District. These designated Ramsar sites are a unique part of the Vembanad-Kole wetland ecosystem. The area remains submerged under flood water for about six months each year, and during the Post and Pre-Monsson seasons, paddy and other agricultural practices are carried out. Additionally, several anthropological activities such as fishing, bird watching, clay mining, building construction, research, and recreation take place in the Kole lands. The Kole wetlands in Thrissur, Kerala, are a rich wetland ecosystem with a diverse range of species. Mosquitoes are an essential part of this ecosystem and are one of the most significant insect disease vectors globally. Mosquitoes thrive and reproduce successfully in wetlands due to the availability of suitable breeding habitats and conducive environments. In Kerala, there has been a significant increase in the outbreak of mosquito-borne diseases in recent years. The presence of mosquitoes in wetlands poses a substantial risk of disease transmission to visitors and workers, thereby becoming a matter of public health concern. It is essential to accurately identify, map, and document the mosquito population and the factors that influence their proliferation to address this issue. This is the initial step in developing an effective vector control strategy. The major study objectives were the diversity study of available mosquito species in the Kole wetlands of Thrissur, Kerala, and compare the susceptibility of Aedes albopictus and Culex quinquefasciatus against conventional insecticides.To understand the mosquito diversity, conventional and molecular identification of available mosquito species, their influencing factors, and GIS preparation of identified mosquito species were done in this study. The larval and adult mosquito populations. ecies were done in this study. The larval and adult mosquito populations XXVIIIwere collected by direct sampling method and identified using systematic keys. A stereo zoom microscope (Leica-M205C) was used for the identification in the laboratory. Dominance D, Simpson's 1-D, Shannon -H, Evenness H/S, Margalef, Biodiversity index, and Berger-Parker indices demonstrated the alpha diversity of the study area. The study involved comparing two sites using the Jaccard and Sorenson Diversity indices and conducting Gamma diversity analysis. The 'PAST' software was utilised for the diversity analysis. The study area had three distinct seasons, namely Pre- monsoon, Monsoon, and Post-monsoon, each lasting four months. Monthly sampling was conducted over a period of two years from each sampling location, and the data collected were recorded. The number of mosquitoes collected in different seasons was analysed using a one-way ANOVA test to determine any variation. GPS readings were taken for each sampling location, and the mosquito species were recorded during the diversity study period. The available mosquito data were used to prepare a GIS map using the QGIS software. Additionally, water samples were collected from larval habitats during the monthly sampling. During the study, water samples were collected and analysed to investigate the relationship between mosquito diversity and the physical and chemical characteristics of the larval habitats. The physico-chemical parameters, including temperature, pH, turbidity, conductivity, and chemical parameters, including total dissolved solids, dissolved oxygen, alkalinity, hardness, chloride, and salinity, were recorded simultaneously with the collection of water samples. The water samples were transported to the laboratory in sterile containers for chemical analysis, and the standard methods recommended by APHA were used to test the water parameters. To ensure the accuracy of identification, molecular identification through CO1 gene sequencing and phylogenetic analysis was conducted. A total of 20 mosquito species from five genera were collected and identified from various locations during the study period. GIS map of 3 sampling sites prepared with these identified mosquito species. The presence and abundance of mosquitoes vary in different seasons. Almost all mosquitoes except Ph. cogilli and Ma. bonneae were collected in either two or three seasons in a year. ANOVA test reveals that nearly all mosquitoes other than four species (An. stephensi, Ph. cogilli, Cx. bitaeniorhynchus, and Ma. bonneae) showed a significant variation in different seasons. Species with no variation were either present in only one season (Ph. cogilli and Ma. bonneae) or had a uniform distribution in two (Cx. bitaeniorhynchus) or three (An. stephensi) seasons. In this study, we tried to analyse the correlation between the physico-chemical parameters of water samples from different breeding habitats and mosquito diversity. Altogether 20 mosquito species were collected from different breeding habitats during the study period, and values of 10 water quality parameters were recorded. pH, Turbidity, Conductivity, TDS, Hardness, and Chloride exhibits significant correlation with the total number of mosquitoes collected. The rest of the parameters (Temperature, DO, Alkalinity, Salinity) do not correlate with the number of mosquitoes collected. Out of 20 species discovered, 9 mosquitoes express some correlation between the physico-chemical parameters of water samples from their breeding habitats. DNA sequencing, molecular identification, and phylogenetic analysis were done with these collected species for species confirmation. Final nucleotide sequences of every collected species were deposited to NCBI GenBank and obtained an accession number. ORIGIN Genomic DNA isolation Kit used for DNA extraction. Agarose gel electrophoresis was conducted for the confirmation of the presence of DNA. The amplification reaction was performed using a DNA thermal cycler (Takara). The purified PCR product was sequenced using Sanger’s sequencing method at Sci Genom Labs Private Ltd., Cochin, and IISc Bengaluru with ABI 3730XL automated sequencer. The trimmed COI sequences of forward and reverse obtained were aligned using ClustralW. The Final sequence was searched in NCBI BLAST for species confirmation. The partial COI gene sequence was deposited in GenBank (NCBI) for worldwide accession, and it can be used as a molecular barcode generation. Final nucleotide sequences were analysed using MEGAX to study phylogenetic relationships. Insecticide susceptibility of Ae. albopictus and Cx. quinquefasciatus against conventional insecticides were checked by the standard WHO method. Comparison analysis of lethal concentration values of field and laboratory strain Ae. albopictus and Cx. quinquefasciatus revealed that laboratory strain was more susceptible than field strain mosquitoes in every insecticide. The remarkable difference in LC 50 values between strains of the same species may be the product of the evolution of insecticide resistance. This trait may be essential as a biological indicator of insecticide pollution. In the context of tested insecticides, synthetic pyrethroids were the most influential group of insecticides, and carbamate was the least effective. The insecticide efficacy varies, and the decreasing order of susceptibility follows Lambda- cyhalothrin > Deltamethrin > Temephos > Malathion > Propoxur. This study will provide information about available mosquito species and the prediction of mosquito- borne disease outbreaks in the Kole wetlands of Thrissur. The findings from the susceptibility test conducted on the identified mosquito species can aid in the efficient management of mosquito populations by minimizing the use of pesticides.
Keywords: Mosquitoes Biology Life Cycle Breeding Habitats Feeding Behaviour Role in Ecology Wetlands Importance of wetlands Wetland Mosquitoes Kole Wetlands GIS preparation with available mosquito species Seasonal variation Physicochemical parameters and mosquito diversity Barcoding and Phylogenetic analysis of mosquitoes Phylogenetic tree and barcode Insecticide susceptibili